The Role of Socioeconomic and Female Indicators on Infant Mortality in West Nusa Tenggara: A Panel VECM Analysis - Arini, Rechtiana Putri; Mumtazah, Soraya Afkarina; Siahaan, Rio Manuppak; Kartiasih, Fitri (Universitas Airlangga, 2024)
West Nusa Tenggara Province has an infant mortality rate that surpasses the national average. Additionally, it is also characterized as having a high Gini ratio and gender inequality index. Therefore, this study aims to examine the differences in classification among different regions, the long-term and short-term impact, and the causal relationship between socio-economic factors and female indicators in relation to infant mortality. This study used the co-integration method of the panel VECM and applied the natural breaks (Jenks) classification method based on panel data from 10 regencies/cities in West Nusa Tenggara Province between 2012 and 2022. This study discovered two instances of co-integration where the life expectancy of women was found to have a negative impact, while the percentage of women working full-time was found to have a positive impact on the long-term infant mortality rate. Infant mortality rates in the short term showed a significant relationship with the cointegration coefficient, mean years of schooling of women, life expectancy of women, and percentage of women working full-time. There is a direct causal relationship between the mean years of schooling of women and the percentage of people living in poverty and the infant mortality rate. This study is expected to serve as a basis to guide the Government of West Nusa Tenggara Province in promoting equity in education, equal job opportunities, adequate healthcare facilities, and increased investment to decrease infant mortality.